RANCANG BANGUN SISTEM ABSENSI DAN NOTIFIKASI MENGGUNAKAN RFID DAN WHATSAPP BLAST DI SMKN 1 KOTA SERANG - Irma Yunita Ruhiawati; Mochamad Yusuf Romdoni (Journal of Innovation And Future Technology (IFTECH), 2021)
School is one of the places that plays an important role in educating a child, especially in matters relating to behavior, intellectual intelligence, emotional intelligence and spiritual intelligence. All of that will be built from an early age which is based in the school environment, therefore how important schools are for children. Vocational High School is a level with education equivalent to Senior High School whose education has a certain field with the aim of graduating ready to work. The attendance or attendance system is needed by schools to assess a student's achievement. However, there is a problem where some schools currently use conventional methods in giving presence to their students, including SMKN 1 Kota Serang. This problem can result in the duration of teaching and learning time being reduced and the resulting data information is inaccurate. With the presence of a computerized attendance system that will make this problem resolved, therefore the authors intend to design and create an attendance or attendance system that facilitates schools, especially in terms of student attendance or attendance. For this study, the authors used Radio Frequency Identification (RFID) as a medium for automatic student attendance combined with web-based applications using the PHP programming language and MySQL Database Management System for processing student attendance data. For the system development method, the author uses the Waterfall method so that it can facilitate the design of the attendance system or student attendance.